A dictionary of literary symbols - Ferber, Michael (Gale virtual reference library, 1999)
A dictionary of nearly 200 symbols found in literature. Focuses on literary references rather than universal psychological archetypes, myths, or esoterica. Also provides cross-references and quotations. Emphasis on English literature. Entries range from the Bible and classical authors to modern-day writing, taking in American and European literatures.